Agonistic autoantibodies against ß2-adrenergic receptor influence retinal microcirculation in glaucoma suspects and patients - Hohberger, Bettina; Hosari, Sami; Wallukat, Gerd; Kunze, Rudolf; Krebs, Johann Ferdinand; Müller, Magdalena; Hennig, Till; Lämmer, Robert; Horn, Folkert; Garcia Munoz, Luis Enrique; Herrmann, Martin; Mardin, Christian (PLoS ONE, 2021)
PURPOSE: Agonistic β2-adrenergic receptor autoantibodies (β2-agAAb) have been observed in sera of patients with ocular hypertension and open-angle glaucoma (OAG). They target the β2-receptors on trabecular meshwork, ciliary body and pericytes (Junemann et al. 2018; Hohberger et al. 2019). In addition to their influence on the intraocular pressure, an association to retinal microcirculation is discussed. This study aimed to investigate foveal avascular zone (FAZ) characteristics by en face OCT angiography (OCT-A) in glaucoma suspects and its relationship to β2-agAAb status in patients with OAG. MATERIAL AND METHODS: Thirty-four patients (28 OAG, 6 glaucoma suspects) underwent standardized, clinical examination including sensory testing as white-on-white perimetry (Octopus G1, mean defect, MD) and structural measures as retinal nerve fibre layer (RNFL) thickness, neuroretinal rim width (BMO-MRW), retinal ganglion cell layer (RGCL) thickness, and inner nuclear layer (INL) thickness with high-resolution OCT. FAZ characteristics were measured by OCT-A scans of superficial vascular plexus (SVP), intermediate capillary plexus (ICP), and deep capillary plexus (DCP). FAZ-R was calculated (area FAZ (SVP)/area FAZ (ICP)). Using cardiomyocyte bioassays we analysed serum samples for the presence of β2-agAAb. RESULTS: (I) Total mean FAZ area [mm2]: 0.34±0.16 (SVP), 0.24±0.12 (ICP), and 0.49±0.24 (DCP); mean FAZ-R 1.58±0.94. No correlation was seen for FAZ-R with MD, RNFL, BMO-MRW, RGCL thickness and INL thickness (p>0.05). (II) ß2-agAAb have been observed in 91% patients and showed no correlation with MD, RNFL, BMO-MRW, RGCL thickness and INL thickness (p>0.05). (III) FAZ-R correlated significantly with the β2-agAAb-induced increase of the beat rate of cardiomyocyte (p = 0.028). CONCLUSION: FAZ characteristics did not correlate with any glaucoma associated functional and morphometric follow-up parameter in the present cohort. However, level of β2-agAAb showed a significantly correlation with FAZ-ratio. We conclude that β2-agAAb might be a novel biomarker in glaucoma pathogenesis showing association to FAZ-ratio with OCT-A.
CRIS-Team Scopus Importer:2021-05-21

APSified OCT-angiography analysis: Macula vessel density in healthy eyes during office hours - Müller, Meike; Schottenhamml, Julia; Hosari, Sami; Hohberger, Bettina; Mardin, Christian Y. (PLoS ONE, 2023)
Purpose Optical coherence tomography angiography (OCT-A) can visualize retinal capillary microcirculation non-invasively. In order to investigate potential factors influencing OCT-A diagnostics, the aim of the present study was to determine circadian changes in macular vessel density (VD) in healthy adults during office hours, considering axial length (AL) and subfoveal choroidal thickness (CT). Methods In the prospective study 30 eyes of 30 healthy subjects (mean age 28.7 ± 11.8, range 19–60 years) were recruited who underwent repeated measurements of AL, subfoveal CT and three-layer macula VD (superficial vascular plexus (SVP), intermediate capillary plexus (ICP) and deep capillary plexus (DCP)) on a single day at three predetermined timepoints (9 AM, 3 PM, and 9 PM). For better intra- and interindividual scan comparability, the new Anatomic Positioning System function (APS, part of Glaucoma Module Premium Edition [GMPE], Heidelberg Engineering, Germany) allowing analysis of identical retinal areas, was used for quantitative OCT-A analysis. Results Overall mean macula VD was unchanged during office hours in SVP, ICP and DCP, respectively (p>0.05). In addition, AL and CT showed no statistically significant changes over time (p>0.05). Rather, a large interindividual variance of VD with different peak time was observed. Contrary to the overall data, sectorial VD changed in dependency of office hours in all layers with an increase of VD in SVP between 9 AM and 9 PM (p = 0.003), in ICP between 3 PM and 9 PM (p = 0.000), in DCP between 9 AM and 9 PM (p = 0.048), and 3 PM and 9 PM (p = 0.000), respectively. Conclusion Overall mean macula VD, subfoveal CT and AL tended not to show statistically significant changes over time in this cohort, whereas a regional analysis of VD did. Therefore, a circadian influence on capillary microcirculation should be kept in mind. Moreover, the results highlight the importance of a more detailed analysis of VD in different sectors and different vascular layers. In addition, the pattern of diurnal variation could vary inter-individually, thus a patient-specific fluctuation pattern would need to be considered when evaluating these parameters in clinical practice.
CRIS-Team Scopus Importer:2023-03-24

Association of the retinal vasculature and intrathecal immunity during relapsing remitting multiple sclerosis - Noll, C.; Aly, L.; Hiltensperger, M.; Wicklein, R.; Mitsdorffer, M.; Herrmann, D.; Gasperi, C.; Herrmann, D.; Gasperi, C.; Berthele, A.; Hosari, Sami; Mardin, Christian Y.; et al. (MULTIPLE SCLEROSIS JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-03

Correlation of retinal vascular characteristics with laboratory and ocular findings in Fabry disease: exploring ocular diagnostic biomarkers - Lindziute, Migle; Kaufeld, Jessica; Hufendiek, Karsten; Volkmann, Ingo; Brockmann, Dorothee; Hosari, Sami; Hohberger, Bettina; Christian, Mirko; Framme, Carsten; Jan, Tode; Hufendiek, Katerina (Orphanet Journal of Rare Diseases, 2023)
Background: The goal of this study was to evaluate macular microvascular changes in patients with Fabry disease (FD) using optical coherence tomography angiography (OCTA) and to explore their correlation with laboratory and ocular findings. Methods: A total of 76 eyes (38 patients) and 48 eyes of 24 healthy controls were enrolled in this prospective study. Vessel Area Density (VAD) and Foveal Avascular Zone (FAZ) area were calculated on 2.9 × 2.9 mm OCTA images scanned with the Heidelberg Spectralis II (Heidelberg, Germany). VAD was measured in three layers: Superficial Vascular Plexus (SVP), Intermediate Capillary Plexus (ICP), and Deep Capillary Plexus (DCP). All scans were analyzed with the EA-Tool (Version 1.0), which was coded in MATLAB (The MathWorks Inc, R2017b). FAZ area was manually measured in full-thickness, SVP, ICP and DCP scans. Results: Average VAD in SVP, ICP and DCP was higher in Fabry disease patients than in controls (49.4 ± 11.0 vs. 26.5 ± 6.2, 29.6 ± 7.4 vs. 20.2 ± 4.4, 32.3 ± 8.8 vs. 21.7 ± 5.1 respectively, p < 0.001). Patients with cornea verticillata (CV) had a higher VAD in ICP and DCP compared to patients without CV (p < 0.01). Patients with increased lysoGb3 concentration had a higher VAD in DCP when compared to patients with normal lysoGb3 concentration (p < 0.04). There was no difference in VAD in patients with and without vascular tortuosity. However, a significantly higher VAD was observed in patients with vascular tortuosity compared to controls (p < 0.03). Conclusions: Increased lysoGb3 and VAD in DCP could be reliable biomarkers of disease activity. Cornea verticillata could be adopted as a predictive biomarker for VAD changes and disease progression. The combination of cornea verticillata and increased VAD may serve as a diagnostic biomarker for Fabry disease, however due to the discrepancies in VAD values in various studies, further research has to be done to address this claim.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Biomarkers; Fabry disease; OCT angiography; Vascular remodelling; Vessel area density

Macular Vessel Density and Foveal Avascular Zone Metrics Using Optical Coherence Tomography Angiography in Fabry Disease. Long Term Follow Up - Hufendiek, Katerina; Lindziute, Migle; Kaufeld, Jessica; Volkmann, Ingo Roland; Brockmann, Dorothee; Hosari, Sami; Hohberger, Bettina; Mardin, Christian Y.; Framme, Carsten; Tode, Jan; Hufendiek, Karsten (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Neutrophil extracellular traps and DNases orchestrate formation of peritoneal adhesions. - Elrod, Julia; Heuer, Annika; Knopf, Jasmin; Schoen, Janina; Schönfeld, Lavinia; Trochimiuk, Magdalena; Stiel, Carolin; Appl, Birgit; Raluy, Laia Pagerols; Saygi, Ceren; Zlatar, Leticija; Hosari, Sami; et al. (iScience, 2023)
Peritoneal adhesions are poorly understood but highly prevalent conditions that can cause intestinal obstruction and pelvic pain requiring surgery. While there is consensus that stress-induced inflammation triggers peritoneal adhesions, the molecular processes of their formation still remain elusive. We performed murine models and analyzed human samples to monitor the formation of adhesions and the treatment with DNases. Various molecular analyses were used to evaluate the adhesions. The experimental peritoneal adhesions of the murine models and biopsy material from humans are largely based on neutrophil extracellular traps (NETs). Treatment with DNASE1 (Dornase alfa) and the human DNASE1L3 analog (NTR-10), significantly reduced peritoneal adhesions in experimental models. We conclude that NETs serve as essential scaffold for the formation of adhesions; DNases interfere with this process. Herein, we show that therapeutic application of DNases can be employed to prevent the formation of murine peritoneal adhesions. If this can be translated into the human situation requires clinical studies.
EVALuna2:551953

NEUTROPHILS AND NETS AS ORCHESTRATORS OF INFLAMMATORY DISEASES - Hosari, D.; Hosari, Sami; Mahajan, Aparna; Oreski, Leticija; Schoen, J.; Shan, Xiaomei; Singh, Jeeshan; Wang, H.; Yaykasli, Kürsat Oguz; Knopf, Jasmin; Munoz, Luis Enrique; Schauer, Christine; et al. (CLINICAL AND EXPERIMENTAL RHEUMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-09-17

OCT angiography: Measurement of retinal macular microvasculature with Spectralis II OCT angiography - reliability and reproducibility - Hosari, Sami; Mardin, Christian; Hohberger, Bettina (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2021-10-18

Retinal vessel loss indicates disability and grey matter atrophy in patients with relapsing remitting multiple sclerosis - Romahn, E. F.; Bussas, M.; Grahl, S.; Noll, C.; Wicklein, R.; Aly, L.; Berthele, A.; Hosari, Sami; Mardin, Christian Y.; Kirschke, J. S.; Zimmer, C.; Korn, T.; et al. (MULTIPLE SCLEROSIS JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-03